Analysis of phosphorous content in cancer tissue by synchrotron micro-XRF. (February 2021) - Falchini, G.E.; Malezan, A.; Poletti, M.E.; Soria, E.; Pasqualini, M.; Perez, R.D.
Abstract: In the present work, an analytical procedure for spatial quantification of phosphorous in cancerous tissues by micro-XRF was developed. This new methodology based on fundamental parameter approach consists of evaluating the incoming microbeam excitation x-ray spectrum on the sample and the matrix effects. The former was determined through a spectral reconstruction technique, based on the scattering pattern of a thin standard plastic material and the latter with the assistance of two transmission monitor ionization chambers. The procedure was applied on fifteen samples of murine gland mammary adenocarcinoma fixed in paraffin. Slices of 30 μm of these samples were scanned at air atmosphere in areas of 5 mm × 5 mm with a spatial resolution of 20 μm. The acquisition time per pixel was 5s allowing a detection limit for phosphorous of 240 ppm w/w. The results showed that the technique is able to detect the elevation of the phosphorous content in tumour tissues, as it was previously reported in the literature using other techniques. In addition, the spatial resolution of the technique allowed associating this increment with areas composed mainly by active tumour cells that were previously identified by Haematoxylin staining. In these areas, phosphorous concentrations showed spatial variations probably associated with tumour metabolism. Thus, micro-XRF offers valuable information of P spatial distribution that could be useful to identify active tumour cells as well as to study of tumour growth and progression. Highlights: A new application of micro-XRF in cancer histology has been found. The micro-XRF can successful quantify local phosphorous in cancer tissues. A strong correlation between phosphorous and active tumour cells has been found. Micro-XRF is viable to follow phosphorous as biomarker of tumour progression.